A rogue's rules for seduction - Leigh, Eva (Leigh, Eva. Last chance scoundrels., 2023)
"When she is thrown together with the man who jilted her at the altar, Lady Willa Ransom tries to deny the still-burning attraction between them, but soon the line between love and loathing begins to blur"--